Composition portfolio - Boesack, Lenrick Jonathan Angus (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2017)
This short composition portfolio comprises 40% of the requirements for the Master of Music Degree in performance and composition at Rhodes University. In addition to the music presented here, I played two public exam recitals of 70 minutes each. While I played piano as a child, my main instrument during my BMUS studies at the University of Cape Town (2004-2007) was the saxophone. In 2010 I was diagnosed with Polymyositis(an auto-immune desease) which particularly affected my breathing and therefore my ability to play the saxophone. For this reason I opted to play my recitals on the piano. The first recital focused on interpretations of Swing Era, Bebop and post-Bebop standards such as: Someday my prince will come, What is this thing called love, In your own sweet way, Eternal Triangle, Recordame, Peace, Dolphin Dance, Caravan and Some other blues. The second recital comprised of seven original compositions that were presented in trio, quartet and quintet settings.
Keywords: Piano music; Prepared piano music; Saxophone music